Effect of soaking and high-pressure processing on antioxidant content, functional and pasting properties of Bambara groundnut (Vigna subterranean (L.) Verdc) flour - Omoniyi, S.A.; Mustapha, N.A.; Shukri, R.; Ramli, N.S.; Sulaiman, R. (Rynnye Lyan Resources, 2024)
The study evaluated the effect of pre-treatment methods on the antioxidant content, functional properties and pasting profile of Bambara groundnut flour. Soaking and high-pressure processing (HPP) were used as pre-treatment methods. The results revealed that the value of crude protein, crude fat, total phenolic compounds, 2,2-Diphenyl-1-picrylhydrazyl, ferric reducing antioxidant power, dispersibility, water absorption index and swelling capacity of HPP pre-treated Bambara groundnut flour were significantly higher than the values obtained for raw and soaked pre-treated Bambara groundnut flour. The application of HPP pre-treatment to Bambara groundnut flour resulted in notable improvements in dispersibility, water absorption index, and swelling power. The pasting curve revealed increased peak viscosities in both soaked and HPP pre-treated samples, particularly highlighting the potential for products requiring enhanced gel strength. Additionally, the HPP pre-treated flour exhibited the shortest peak time, suggesting faster cooking and underscoring its versatility in various applications.